2018
DOI: 10.1002/crat.201700150
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermoelectric Properties of Zn‐Doped Sn‐Based Type‐VIII Single‐Crystalline Clathrate via a Grey Sn‐Flux Method

Abstract: A single‐crystalline samples of Zn‐substituted type‐VIII clathrate Ba8Ga16Sn30 with n‐type carriers by α‐Sn flux method according to the formula Ba8Ga16ZnxSn30 (x = 0, 0.5, 1, and 1.5) is grown. It is found that as the amount of Zn increases from 0.025 to 0.155, the content of Ga decreases from 15.18 to 14.72, indicating Zn atoms preferentially replacing Ga. The carrier concentrations of obtained samples vary from 3.55 × 1019 to 5.53 × 1019 cm−3 as carrier mobility changes from 14.7 to 20.9 cm2 · V−1 · s−1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Benefiting from rational thermoelectric designs, significant progress has been made on high-performance and cost-effective thermoelectric materials. Figure a presents the reported state-of-the-art thermoelectric materials with maximum ZT values ( ZT max ), cost, and cost-effectiveness ( ZT max /cost), including clathrates, GeTe, half-Heuslers, Bi 2– x Sb x Te 3 (BST), , SnTe, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefiting from rational thermoelectric designs, significant progress has been made on high-performance and cost-effective thermoelectric materials. Figure a presents the reported state-of-the-art thermoelectric materials with maximum ZT values ( ZT max ), cost, and cost-effectiveness ( ZT max /cost), including clathrates, GeTe, half-Heuslers, Bi 2– x Sb x Te 3 (BST), , SnTe, …”
Section: Introductionmentioning
confidence: 99%
“…Notably, high ZT max values of ≥2.4 were reported in some of the thermoelectric materials, such as GeTe, ,, PbTe, , SnSe, ,, and Cu 2 Se. ,,, However, part of these materials with high ZT max values have not exhibited high reproducibility; thus they are controversial with either unclear mechanisms or improper evaluations of thermoelectric properties. Figure b summarizes the ZT values of these materials measured in the last decade, , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…431 Finally, one report on a type-VIII clathrate (G 8 [F 46 ]; own type, space group I43m) has been published, which investigated the substitution in Ba 8−x Yb x Ga 16 Sn 30 . 432 Here, an improvement of the Seebeck coefficient up to x = 1.0 was observed. Overall, the situation is similar to the type-I clathrates: a substitution adjusts the Seebeck coefficient as well as the electrical and thermal conductivity, leading to an improvement of the figure of merit zT.…”
Section: Zintl Phasesmentioning
confidence: 64%
“…For instance, Chen et al obtained a ZT value of 0.91 at 900 K for Yb doped Ba 7.79 Yb 0.21 Ni 0.07 Zn 0.38 Ga 14.02 Ge 30.25 . Shen et al reported ZT value of 0.63 at 537 K for Zn‐doped Ba 8 Ga 16 Sn 30 , and ZT value of 0.52 was obtained in Ge doped Ba 8 Ga 16 In x Ge 30‐x by Liu et al Moreover, material synthesis processes also play a significant role in enhancing the overall performance of these materials. For instance, Wang et al prepared p‐ type Ba 8 Ga 16 Ge 30 from the melt by the vertical Bridgman method, where the melt was controlled, to prepare Ba 8 Ga 16 Ge 30 poly‐crystals with varying Ga/Ge atomic ratios.…”
Section: High Performance Inorganic Te Materialsmentioning
confidence: 99%